PSYCHOLOGICAL CHARACTERISTICS OF BULLYING MANIFESTATIONS IN YOUNG SCHOOL-AGED CHILDREN - Berdiyeva Gulmira Juraevna; Ergasheva Aziza Rajabali qizi (Innovate Conferences, 2025)
This comprehensive study investigates the psychological foundations and characteristics of bullying behavior in children of primary school age, typically between 7 and 10 years old. The research uses a mixed-methods approach that includes quantitative diagnostics and qualitative interviews. Psychological tools such as the Strengths and Difficulties Questionnaire, the Emotion Regulation Checklist, and the Social Position Test by Schneider were used to identify patterns of aggression, victimization, and passive observation. The findings highlight the critical importance of emotional support structures, inclusive peer programs, and school-wide intervention strategies.
Keywords: Bullying, emotional regulation, empathy, child development, school climate, diagnostics, intervention